Measuring Knowledge Spillovers Using Belgian EPO and USPTO Patent Data - Joseph Plasmans; Ruslan Lukatch (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper investigates two major issues of the patenting behavior of Belgian firms. Firstly, it studies the probabilistic distribution of the patent citations among several major sectors. Secondly, the firm-oriented data is studied to investigate the relationships between the Belgian firms' size and their patent citation behavior. The modeling results conclude that there is evidence that the smaller firms tend to be more active in patent citation than larger ones. Analyzing the implications from the probabilistic models of citations the paper concludes, that there are different patterns of citation behavior in different sectors. Some sectors exhibit more openness toward inter-firm or inter-industry spillovers, while others do not. Moreover, different industrial sectors exhibit different relationships between the probability of a citation to occur in this sector and the relative time lag between the citing and cited patents.
Keywords: 330